1980
DOI: 10.1177/107769908005700409
|View full text |Cite
|
Sign up to set email alerts
|

Recall and Comprehension of Radio News in Kenya

Abstract: College students recalled more radio neu's stories than did illiterates, tenth graders or adults uith less than college; comprehension also Mias lower in the latter group in this study done in Kenya.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other studies, however, support stronger primacy effects. Stauffer, Frost, and Rybolt (1980) found that, among 13 news stories, recall was the best for the first item, which was remembered by 49% of the participants.…”
Section: Message Order Effects On Memorymentioning
confidence: 93%
“…Other studies, however, support stronger primacy effects. Stauffer, Frost, and Rybolt (1980) found that, among 13 news stories, recall was the best for the first item, which was remembered by 49% of the participants.…”
Section: Message Order Effects On Memorymentioning
confidence: 93%
“…Repetition does seem to improve recall as does a delivery rate of between 160 and 200 words per minute (Findahl & Hoijer, 1975;Smith & McEwen, 1974). Research also has shown that 20% to 50% of radio newscast items are remembered (Stauffer, Frost, & Rybolt, 1980). This study was conducted to update previous research about the effect of actualities on the recall of radio newscasts and to measure the effect of actualities on the degree of interest listeners have in a radio newscast.…”
mentioning
confidence: 99%